2013
DOI: 10.1016/j.febslet.2013.01.065
|View full text |Cite
|
Sign up to set email alerts
|

Observation of unphosphorylated STAT3 core protein binding to target dsDNA by PEMSA and X‐ray crystallography

Abstract: Edited by Ivan Sadowski Keywords:Signal transducer and activator of transcription 3 STAT3 PEMSA M67 SH2 X-ray crystallography a b s t r a c tThe STAT3 transcription factor plays a central role in a wide range of cancer types where it is overexpressed. Previously, phosphorylation of this protein was thought to be a prerequisite for direct binding to DNA. However, we have now shown complete binding of a purified unphosphorylated STAT3 (uSTAT3) core directly to M67 DNA, the high affinity STAT3 target DNA sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
79
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 28 publications
(39 reference statements)
5
79
0
Order By: Relevance
“…8) phosphorylation (38). Furthermore, recent studies using both atomic force microscopy and X-ray crystallography have directly visualized U-STAT3 binding to GAS elements as an unphosphorylated dimer (37,45 (46). However, the same study also showed that IFN-␥ strongly induces STAT3 Tyr 705 phosphorylation but does not elicit STAT3 binding to the EGR1 promoter, consistent with our results for IL-6 ( Fig.…”
Section: Discussionsupporting
confidence: 91%
“…8) phosphorylation (38). Furthermore, recent studies using both atomic force microscopy and X-ray crystallography have directly visualized U-STAT3 binding to GAS elements as an unphosphorylated dimer (37,45 (46). However, the same study also showed that IFN-␥ strongly induces STAT3 Tyr 705 phosphorylation but does not elicit STAT3 binding to the EGR1 promoter, consistent with our results for IL-6 ( Fig.…”
Section: Discussionsupporting
confidence: 91%
“…This is in contrast to the antiparallel dimers of latent STAT1 and STAT5 where the SH2 domains are localized at the opposite ends of the dimer (Mao et al, 2005;Mertens et al, 2006;Neculai et al, 2005). This parallel association could explain why, under some circumstances, latent STAT3 is capable of DNA binding (Nkansah et al, 2013;Timofeeva et al, 2012) and gene induction (Yang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, this form of STAT6 CF neither bound DNA nor did it crystallize after extensive screening. These features of STAT6 are unlike STAT1 and STAT3, which are known to bind DNA regardless of phosphorylation (11,16). Because the unphosphorylated STAT6 CF did not bind DNA, we produced phosphorylated STAT6 CF as described previously (17,18) (Fig.…”
Section: Phosphorylated Stat6mentioning
confidence: 99%
“…S4K). We aligned the DBD of our STAT6 CF -N3 complex structure with the other three reported STAT protein structures in complex with N3 site DNA, i.e., STAT1 (PDB ID code 1BF5) and STAT3 (PDB ID codes 1BG1 and 4E68) (9)(10)(11). Although the proteins exhibit some flexibility, the position of the key residue, H415 in STAT6, N460 in STAT1, and N466 in STAT3, in both the protomers within the dimer of these STATs overlaps (Fig.…”
Section: Phosphorylated Stat6mentioning
confidence: 99%
See 1 more Smart Citation